MENUMBUH KECINTAAN PEKERJAAN PERTANIAN BAGI GENERASI Z (GEN-Z) PADA LAHAN TERASIRING DENGAN SMART MACHINE PORTABEL MULTIFUNCTION - Hidayat, Tofik; Zulfah, Zulfah; Siswiyanti, Siswiyanti; Sugiono, Moh. Cipto; Nurwildani, Moh. Fajar; Mustaqim, Mustaqim (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Education has shifted the work mindset of Generation Z (Gen-Z) in mountainous areas. A fairly good education, for example a high school/vocational school graduate, has shifted the desire to become a worker in the non-agricultural industrial sector, leaving behind the agricultural work that his parents started. From the preliminary survey, the main reason is actually the hard work of being a rice farmer on mountain slopes or terraced land. Many agricultural machines (agricultural tools) that have been created, starting from plows, rice harvesters and rice threshers, are still dominated for agricultural land in flat areas. This can be seen from the size of the existing machines which are very large and very difficult to use on terraced land. The application of smart machine technology is to make the rice harvesting process easier. The aim of this service is to foster a love of agricultural work for Gen-Z and to create food self-sufficiency. This service methodology starts from designing, manufacturing rice cutting and threshing machines, simulating and practicing. Then they will be taken to the service location to socialize on the use of the machine and the benefits that will be obtained by farmers. At the time of this service implementation, the service location in Tlahab Lor Village, Karangreja District, Purbalingga Regency, did not yet have rice ready to be harvested, therefore the service implementation only showed how the machine worked. It is said to be a smart machine because this machine has 3 (three) functions, namely cutting rice stalks, threshing rice and its main function is cutting grass. This machine is also portable because it only weighs less than 15 kg so it can be carried by itself to the harvest location in a terraced rice field model